Modeling Of A Surface Contact Stress For Spur Gear Mechanism Using Static And Transient Finite Element Method - F. R. M., Romlay (2008)
This paper presents a surface contact static stress of a spur gear system combined with dynamic characteristic using transient Finite Element Method (FEM). Traditionally, the static stress analysis is done separately with dynamic properties due to limitation of complex equation and avoiding of error occurred. However, in this paper, static stress information is combined with the dynamic mechanism due to the time consuming during the design and analysis stage. A transient FEM analysis is carried out to formulate and solve large systems of algebraic equations in order to obtain a relationship between the contact parameter and the kinematics function. The methodology of the research is started with static stress analysis on tooth surface contact of a pair of the spur gear. Finite element modeling is run by choosing a certain static condition. The loading conditions are applied suitable with the gear mechanism. Degree of freedom controlled is based on the transmission system. The process is repeated until diagnosing work is satisfied. The result of the surface contact stress is visualized at each condition. Modeling of spur gear system is continued by combining stress analysis with dynamic characteristic via transient finite element method. Analysis of gear mechanism is obtained by investigate the stress distribution on real time application. Time range is set at the beginning of the analysis. Duration of the analysis is depended on a time frame chosen. By the transient FEM analysis, the stress occur at each step of the work cycle is performed. Results of the kinematics functions are derived and qualitative kinematics variations due to contact changes in time-step domain is identified. The simulation results from static and transient FEM are compared due to the validating procedure. The finite element results are in good agreement compared with the theory calculation.